A SIGE-SINGEM-AIGO technical review on the clinical use of esophageal reflux monitoring. Issue 9 (September 2020) - Savarino, Edoardo; Frazzoni, Marzio; Marabotto, Elisa; Zentilin, Patrizia; Iovino, Paola; Costantini, Mario; Tolone, Salvatore; Battaglia, Edda; Cicala, Michele; Usai-Satta, Paolo; de Bortoli, Nicola; Penagini, Roberto; et al.
Abstract: Patients with esophageal symptoms potentially associated with gastroesophageal reflux disease such as heartburn, regurgitation, chest pain, or cough represent one of the most frequent reasons for referral to gastroenterological evaluation. The utility of esophageal reflux monitoring in clinical practice is: (1) to accurately define reflux burden, (2) to segregate patients according to reflux monitoring results as true GERD, reflux hypersensitivity and functional heartburn, and (3) to establish a treatment plan. With this in mind, in the last decade, investigations and technical advances, with the introduction of impedance-pH monitoring and wireless pH capsule, have enhanced our understanding and management of GERD. The following recommendations were discussed and approved after a comprehensive review of the medical literature pertaining to reflux testing techniques and their recent application. This review created under the auspices of the Società Italiana di Gastroenterologia ed Endoscopia Digestiva (SIGE), Società Italiana di Neuro-Gastro-Enterologia e Motilità (SINGEM) and Associazione Italiana Gastroenterologi ed Endoscopisti Digestivi Ospedalieri (AIGO) is intended to help clinicians in applying reflux studies in the most fruitful manner within the context of their patients with esophageal symptoms.